2008
DOI: 10.1007/s00253-008-1364-y
|View full text |Cite
|
Sign up to set email alerts
|

NADH- vs NADPH-coupled reduction of 5-hydroxymethyl furfural (HMF) and its implications on product distribution in Saccharomyces cerevisiae

Abstract: Saccharomyces cerevisiae alcohol dehydrogenases responsible for NADH-, and NADPH-specific reduction of the furaldehydes 5-hydroxymethyl-furfural (HMF) and furfural have previously been identified. In the present study, strains overexpressing the corresponding genes (mut-ADH1 and ADH6), together with a control strain, were compared in defined medium for anaerobic fermentation of glucose in the presence and absence of HMF. All strains showed a similar fermentation pattern in the absence of HMF. In the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
83
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(87 citation statements)
references
References 28 publications
1
83
0
3
Order By: Relevance
“…The improved ethanol production from co-utilization of xylose and acetate was also demonstrated in synthetic medium and corn stover hydrolysates ( Supplementary Figs S9 and S10). In lignocellulosic hydrolysates, reduction of alternative electron acceptors such as furaldehyde compounds might also help improve xylose fermentation [31][32][33] . However, acetate reduction still occurred in the hydrolysates and improved ethanol yields by strain S-adhE as compared with S-nc, …”
Section: Resultsmentioning
confidence: 99%
“…The improved ethanol production from co-utilization of xylose and acetate was also demonstrated in synthetic medium and corn stover hydrolysates ( Supplementary Figs S9 and S10). In lignocellulosic hydrolysates, reduction of alternative electron acceptors such as furaldehyde compounds might also help improve xylose fermentation [31][32][33] . However, acetate reduction still occurred in the hydrolysates and improved ethanol yields by strain S-adhE as compared with S-nc, …”
Section: Resultsmentioning
confidence: 99%
“…Thus, an effective microbial furfural reduction system has the potential to increase resistance to furfural. Furfural-resistant strains of S. cerevisiae have been isolated (2,20,22,23) and found to exhibit increased expression of aldehyde reductases, which may contribute to tolerance. In E. coli, many oxidoreductases were also induced by furfural, but none originally tested were found to reduce toxicity when overexpressed in the parent strain (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Furan alcohols (reduced products) are less toxic than the respective aldehydes (39,40). Several genes encoding oxidoreductases that reduce furfural and 5-hydroxymethylfurfural (5-HMF) (a dehydration product of hexose sugars) have been implicated in furan tolerance in Saccharomyces cerevisiae (2,20,21,22,23) and in Escherichia coli (29)(30)(31)38). Gene array studies identified more than 365 genes that changed in expression level during an HMF challenge, and these changes are proposed to be mediated by at least 5 different regulatory genes (24).…”
mentioning
confidence: 99%
“…On the other hand, furfural and HMF can also be detoxified by oxidation by Ald6 aldehyde dehydrogenase (13). In line with these detoxification mechanisms, furfural-and/or HMF-tolerant yeast strains could be generated by the overexpression of ADH6, ADH7, and ALD6 (6,7,13). In addition, overexpression of ZWF1, involved in NADPH regeneration through a pentose phosphate pathway, also enhanced furfural tolerance (15).…”
mentioning
confidence: 98%
“…These furan aldehydes are known as the most potent inhibitors of microbial cell growth (4,5). The toxic aldehyde groups of furfural and HMF can be reduced to hydroxyl groups by several oxidoreductases, including alcohol dehydrogenases (Adh1, Adh6, and Adh7) (6)(7)(8), aldehyde reductase (Ari1) (9), and methylglyoxal reductases (Gre2 and Gre3) in Saccharomyces cerevisiae cells (8,(10)(11)(12)(13) and aldehyde dehydrogenase (YqhD) and methylglyoxal reductase (DkgA) in Escherichia coli (14). These enzymes consume NADH and NADPH as cofactors during the reduction process.…”
mentioning
confidence: 99%